2005
DOI: 10.1002/pbc.20602
|View full text |Cite
|
Sign up to set email alerts
|

Multiple behavioral risk factors among adolescent survivors of childhood cancer in the Survivor Health and Resilience Education (SHARE) Program

Abstract: The evidence suggests interventions to reduce multiple health-compromising behaviors in these patients are warranted, and that efforts to address these patients' personal and family stress levels are important as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 32 publications
3
61
0
5
Order By: Relevance
“…Despite these recommendations, many survivors do not practice adequate sun protection [20][21][22], and younger survivors appear to be least likely to follow sun protection recommendations. A recent Childhood Cancer Survivor Study (CCSS) report, which examined several specific sun protection behaviors (e.g., artificial tanning, hat wearing, etc.…”
mentioning
confidence: 89%
“…Despite these recommendations, many survivors do not practice adequate sun protection [20][21][22], and younger survivors appear to be least likely to follow sun protection recommendations. A recent Childhood Cancer Survivor Study (CCSS) report, which examined several specific sun protection behaviors (e.g., artificial tanning, hat wearing, etc.…”
mentioning
confidence: 89%
“…These survivors may be engaging in adverse drinking behaviors to cope with the stresses of life (21). Interventions that help survivors cope with stress and the psychological strain of Cancer Epidemiology, Biomarkers & Preventiontheir cancer may also encourage adoption of healthy lifestyle choices (35). The weekly and harmful drinking recommendations used in our study were those intended for the general population, but it is possible that risks to health from alcohol may start to increase from different levels of consumption depending on other health risks (11), and it is suggested that no level of alcohol consumption is riskfree in relation to cancer incidence (36).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent cancer survivors are at risk for experiencing cognitive late effects, high-risk health behaviors, and increased rates of family stress, anxiety, and posttraumatic stress disorder compared with children and older adults. 56,57 It is possible that these cognitive, emotional, behavioral, and family dynamic concerns may be associated with adherence. 36,56,[58][59][60][61][62] The influence of peer relationships on adherence, compared with those with parents and providers, should also be further examined for adolescents diagnosed with cancer.…”
Section: Psychosocial Barriers and Facilitators Affecting Adherence Tmentioning
confidence: 99%